2012
DOI: 10.1080/02640414.2011.630744
|View full text |Cite
|
Sign up to set email alerts
|

Varsity athletes have lower 2D:4D ratios than other university students

Abstract: The second to fourth digit ratio (2D:4D) is a sexually dimorphic trait with lower finger ratios considered more masculine. These digit ratios are believed to reflect the prenatal hormonal environment with higher exposure to androgens in utero leading to more masculine digit ratios. The 2D:4D ratio has been negatively correlated with many factors, including aggression, physical fitness, and athleticism. We compared 2D:4D finger ratios of (1) male and female varsity athletes (n = 99) versus male and female stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
2
26
0
1
Order By: Relevance
“…[9] for gymnasts and with those on other measures of sporting abilities in women such as ergometer rowing performance [7], national or international fencing ranking with left 2D:4D [2], [11], and handgrip strength [23], [24]. However they are in contrast with studies in which significant relationships between 2D:4D and sporting ability in females were observed with the dominant hand 2D:4D [3], the left hand 2D:4D [21], or the right hand 2D:4D [2], [11], [22] although none of these studies contrasted world-class elite athletes with sedentary reference samples.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…[9] for gymnasts and with those on other measures of sporting abilities in women such as ergometer rowing performance [7], national or international fencing ranking with left 2D:4D [2], [11], and handgrip strength [23], [24]. However they are in contrast with studies in which significant relationships between 2D:4D and sporting ability in females were observed with the dominant hand 2D:4D [3], the left hand 2D:4D [21], or the right hand 2D:4D [2], [11], [22] although none of these studies contrasted world-class elite athletes with sedentary reference samples.…”
Section: Discussionmentioning
confidence: 67%
“…Overall, results of the studies are not consistent and in part difficult to compare because of the use of different procedures for measuring the digit lengths. In some studies where both sexes are included the relation is found in both men and women [3], [18], [22], although in the study of Hönekopp et al [18] the relation in women was significant only for the left hand 2D:4D and not for the right hand 2D:4D and vice versa in men. Other studies found a significant relation in men but not in women [7] and vice-versa [11].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The association between 2D:4D ratio and a variety of adult phenotypes has been explored. The most robust have included a lower 2D:4D ratio associated with athletic ability [25][26][27] and with autism spectrum disorders. 28,29 Regarding neurologic diseases, in men a higher 2D:4D ratio has been linked with higher risk of Alzheimer disease, while a lower 2D:4D ratio was associated with risk in women.…”
Section: Ms Clinical Outcomesmentioning
confidence: 99%
“…Athletes' right hand 2D:4D averages were found as 0.86 and left hand 2D:4D averages were found as 0.93, while sedentary group's right hand 2D:4D averages were found as 0.92 and left hand 2D:4D averages were found as 0.92. In their study, Giffin et al, (2012), found the 2D:4D ratios of varsity athletes as 0.97, while 2D:4D ratios of non-varsity athletes was 0.99 and they reported that varsity athletes had significantly lower ratios than their non-varsity peers. Keshavarz et al, (2017), found that right hand 2D:4D average of elite Greco-Roman wrestlers was 0.93, while their left hand 2D:4D average was 0.93; right hand 2D:4D average of non-elite Greco-Roman wrestlers was 0,97, while their left hand 2D:4D average was 0,98 and right hand 2D:4D average of control group was 0,98, while their left hand 2D:4D average was 0,99.…”
Section: Discussionmentioning
confidence: 94%